Implementation of a speed and torque control on quadrotor altitude and attitude stability - Dollosa, Christian Michael G. (Animo Repository, 2013)
Quadrotor control is a difficult exercise both in terms of theory and application as the stability and ability to hover of the under-actuated vehicles is an immediate result of the effectiveness of the control system. Most quadrotor flight controllers make use of an attitude control loop which is responsible for stabilizing the flight of the vehicle by directly driving the four motors via the electronic speed controllers (ESCs). Such a control loop loses some of its effectiveness when the motors and ESCs are not well matched resulting in variation of the control performance. This study presents an alternative control structure which incorporates an inner speed and torque control loop within the attitude and altitude loop in order to achieve better flight stability and maneuverability. The control structure is designed to make use of PID control on order to correct for errors in the process and to drive the motors correspondingly. The control system is simulated and tuned using Simulink and later implemented digitally on a dsPIC33 microcontroller which is turn is interfaced to the various feedback and instrument sensors. The attitude feedback, the most complicated to achieve, is implemented using a complementary filter to fuse the accelerometer and gyrometer data in order to arrive at usable attitude estimates. The result of the flight testing reveals that the experimental and simulation vary only by an standard deviation of less than 5 degrees and an altitude standard deviation of 50 cm and that the control structure works as intended. The control structure not only compensates for motor and ESC mistakes but also allows the attitude control loop, the one whose effects on the stability is most visible, to operate at the range of operation at which it was tuned at.